Homozygous TBC1D24 Mutation in a Case of Epilepsia Partialis Continua - Zhou, Qilin; Lin, Yicong; Ye, Jing; Li, Liping; Hu, Ningning; Wang, Di; Wang, Yuping (Frontiers in Neurology, 2018)
TBC1D24 mutation related epileptic syndrome includes a wide spectrum of epilepsies. We describe a case with a homozygous TBC1D24 mutation inherited from consanguineous parents. The patient manifested epilepsia partialis continua (EPC) and rare secondary generalized tonic-clonic seizure without intellectual disability or developmental delay. EPC, which involved focal limbs, came with waking and went with sleep. The genetic analysis reported a novel mutation in the TBC1D24 gene, c.229_240del (p.82_84del). The homozygous mutation was inherited from her healthy parents who were heterozygous. Morphometric analysis program (MAP), an MRI post-processing technique, was used and detected a subtle abnormality of the brain. A comprehensive analysis based on semiology, EEG, SEP and MAP suggested a potential focal structural abnormality. This case indicates a possible correlation between the TBC1D24 mutation and brain development abnormality.